The Sealed Palace: How Direct Access to the Supreme Constitutional Court Can Bridge the Gaps in Constitutional Review in Egypt - Fahmi, Ahmed Sameh (AUC Knowledge Fountain, 2025)
This thesis examines the limitations of Egypt’s current constitutional review system and argues for the introduction of a direct access mechanism to the Supreme Constitutional Court (SCC). Under Egypt’s centralized model of judicial review, individuals are restricted to indirect access through ordinary courts, which has resulted in significant procedural and substantive inefficiencies. The referral-based mechanism of judicial review of legislation has caused delays in adjudicating constitutional claims, the insulation of certain laws from review, legislative omissions, and excessive gatekeeping by lower courts. Through a comparative analysis of direct access models in Colombia, Germany, Turkey, and South Africa, the thesis identifies alternative procedural frameworks that have enhanced judicial efficiency and individual rights protection in those jurisdictions. It evaluates their potential for adaptation to the Egyptian context. Building on these insights, the thesis proposes a tailored direct access mechanism for Egypt’s SCC, outlining the necessary legal foundations, scope of admissibility, and safeguards to balance accessibility with judicial efficiency. The study also addresses potential objections, such as concerns over caseload and politicization, and offers counterarguments grounded in comparative experience and Egypt’s constitutional context. Ultimately, the thesis argues that introducing a direct access procedure would bridge critical gaps in Egypt’s constitutional review system, strengthen the rule of law, and align Egypt with global best practices in constitutional justice.